2021
DOI: 10.1017/s1368980021000768
|View full text |Cite
|
Sign up to set email alerts
|

Body size preferences for women and adolescent girls living in Africa: a mixed-methods systematic review

Abstract: Objective: To synthesise evidence on body size preferences for females living in Africa and the factors influencing these. Design: Mixed-methods systematic review including searches on Medline, CINHAL, ASSIA, Web of Science and PsycINFO (PROSPERO CRD42015020509). A sequential-explanatory approach was used to integrate quantitative and qualitative findings. Setting: Urban and rural Africa. Participants: Studies of both sexes providing data on body size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 118 publications
(482 reference statements)
2
30
0
Order By: Relevance
“…A thin body stature was described as primarily desirable among the young. A related systematic review similarly reports that acculturative stress to look slimmer was only reported by younger women and adolescents (Pradeilles et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A thin body stature was described as primarily desirable among the young. A related systematic review similarly reports that acculturative stress to look slimmer was only reported by younger women and adolescents (Pradeilles et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, in Ghana people face a number of other competing nutrition and health challenges such as malaria, HIV/ AIDS, diarrheal diseases, and stunting in children. And some studies have demonstrated an acceptance of overweight -though not extreme overweight -for women in Ghana (Aryeetey, 2016;Tuoyire et al, 2018), and Africa more broadly (Pradeilles et al, 2021). Furthermore, gendered barriers to maintaining a healthy weight include time and cultural barriers to physical activity and cultural norms related to women's weight especially before and after childbirth (De-Graft Aikins, 2011;Elvis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis to explain the variability of effect could be that INSTIs sensitize PLWH to gaining weight, the melanocortin-4 receptor pathway being one proposed mechanism [9]. However, absolute gains are probably influenced by lifestyle [10], cultural attitudes to weight [11], the individual's perception of their weight [12], and host genetics/microbiome [13]. This may explain why weight gain is not a universal phenomenon for all individuals on ART and for all regimens [14].…”
Section: Discussionmentioning
confidence: 99%
“…Both physical and sociocultural environments can favor obesity. A greater access to processed energy-dense foods and motorized transports favors obesogenic dietary practices and sedentary behaviors [7,8], while the traditional social valorization of stoutness and idleness, as symbols of prosperity and peacefulness, leads to obesogenic fattening practices in urban environments [9]. However, the respective and combined contributions of these socioecological determinants remain insufficiently explored, and few studies include all of them in the same multivariable analyses [10].…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increase in the number of studies analyzing these "determinants of determinants"-through body weight perception, dietary intake, and physical activity. Many of these studies were recently synthesized in several systematic reviews focusing on African women's health [9,20,21].…”
Section: Introductionmentioning
confidence: 99%